The time-dependent generalized active space configuration interaction approach to correlated ionization dynamics of diatomic molecules. (March 2016) - Bauch, S; Larsson, H R; Hinz, C; Bonitz, M
Abstract: In this contribution, we review the time-dependent generalized-active-space configuration interaction (TD-GAS-CI) approach to the photoionization dynamics of atoms and molecules including electron correlation effects. It is based on the configuration interaction (CI) expansion of the many-body wave function and the restriction of the determinantal space to a reduced subspace. For its numerically efficient application to photoionization, a partially-rotated basis set is used which adopts features of a localized basis with a good reference description and a grid representation for escaping wave packets. After reviewing earlier applications of the theory, we address the strong-field ionization of a one-dimensional model of the four-electron LiH molecule using TD-GAS-CI and demonstrate the importance of electron-electron correlations in the ionization yield for different orientations of the molecule w.r.t the peak of the linearly polarized laser field. A pronounced orientation-dependent variation of the yield with the pulse duration and the level of considered electron-electron correlations is observed.